Editor's Choice – Update of the European Society for Vascular Surgery (ESVS) 2020 Clinical Practice Guidelines on the Management of Acute Limb Ischaemia in Light of the COVID-19 Pandemic, Based on a Scoping Review of the Literature. (January 2022) - Jongkind, Vincent; Earnshaw, Jonothan J.; Bastos Gonçalves, Frederico; Cochennec, Frederic; Debus, E. Sebastian; Hinchliffe, Robert; Menyhei, Gabor; Svetlikov, Alexei V.; Tshomba, Yamume; Van Den Berg, Jos C.; Björck, Martin
Abstract : Objective: To perform a scoping review of how patients with COVID-19 are affected by acute limb ischaemia (ALI) and evaluate the recommendations of the 2020 ESVS ALI Guidelines for these patients. Methods: Research questions were defined, and a systematic literature search was performed following the PRISMA guidelines. Abstracts and unpublished literature were not included. The definition of ALI in this review is in accordance with the ESVS guidelines. Results: Most identified papers were case reports or case series, although population based data and data from randomised controlled trials were also identified. In total, 114 unique and relevant papers were retrieved. Data were conflicting concerning whether the incidence of ALI increased, or remained unchanged, during the pandemic. Case reports and series reported ALI in patients who were younger and healthier than usual, with a greater proportion affecting the upper limb. Whether or not this is coincidental remains uncertain. The proportion of men/women affected seems unchanged. Most reported cases were in hospitalised patients with severe COVID-19. Patients with ALI as their first manifestation of COVID-19 were reported. Patients with ALI have a worse outcome if they have a simultaneous COVID-19 infection. High levels of D-dimer may predict the occurrence of arterial thromboembolic events in patients with COVID-19. Heparin resistance was observed. Anticoagulation should be given to hospitalised COVID-19 patients in prophylactic dosage. Most of the treatment recommendations from the ESVS Guidelines remained relevant, but the following were modified regarding patients with COVID-19 and ALI: 1) CTA imaging before revascularisation should include the entire aorta and iliac arteries; 2) there should be a high index of suspicion, early testing for COVID-19 infection and protective measures are advised; and 3) there should be preferential use of local or locoregional anaesthesia during revascularisation. Conclusion: Although the epidemiology of ALI has changed during the pandemic, the recommendations of the ESVS ALI Guidelines remain valid. The above mentioned minor modifications should be considered in patients with COVID-19 and ALI.